FINANCIAL LITERACY DAN OVERCONFIDENCE DALAM KEPUTUSAN INVESTASI - Abdillah Rabbani, Inayah; Saputra, Idul (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
The rapid growth of Indonesia's capital market shows the increasing awareness of investors about the importance of investing. An investment decision is based on intuition that is present in the individual based on experience, beliefs, and skills. This study aims to determine whether the understanding of financial literacy and the occurrence of overconfidence affect individual decisions to investation. The research based quantitative model by information all members of the KSPM (Capital Market Study Group) at Halu Oleo University who have been registered as capital market investors on the IDX as many as 40 people as research respondents. The information used is based on the results of online questionnaire response processing which is processed using multiple linear regression analysis.The study shows that financial literacy and overconfidence have a significant positive effect on investment decisions. It’s means that investment decisions occur because investors have good financial literacy and there is overconfidence as a belief that encourages individuals to invest.